2015
DOI: 10.1097/pts.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Triad Vii

Abstract: In the Pennsylvania prehospital setting, POLST documents can be confusing, presenting a risk to patient safety. Additional research, standardized education, training, and/or safeguards are required to facilitate patient choice and protect safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…7 ,8 Thus, these studies yield 2 concerning conclusions. First, by allowing potentially confusing combinations of orders, POLST could cause patients to receive care that is either more or less aggressive than patients preferred when the documents were completed.…”
Section: Clarity Of Interpretationmentioning
confidence: 75%
See 2 more Smart Citations
“…7 ,8 Thus, these studies yield 2 concerning conclusions. First, by allowing potentially confusing combinations of orders, POLST could cause patients to receive care that is either more or less aggressive than patients preferred when the documents were completed.…”
Section: Clarity Of Interpretationmentioning
confidence: 75%
“…In the recent TRIAD VI and VII studies, 7, 8 emergency physicians (n = 223) and out-of-hospital personnel(n = 1069) were asked to interpret sample POLST forms with different combinations of orders. Study participants were then asked to state how they would treat a patient who presented with each form.…”
Section: Clarity Of Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a lack of confidence and knowledge about ACP among GPs affecting the initiation of ACP 49 and among paramedics affecting interpretation of ACP. 50 Our study adds further evidence demonstrating that lack of staff understanding of ACP can contribute to unsafe and inappropriate care. More research is needed to understand how to enable clinicians to create and use high-quality ACP to guide decision-making.…”
Section: Cross-cutting Themes and Consequences-interpretative Synthesmentioning
confidence: 51%
“…In the recent TRIAD VI and VII studies, health care workers inconsistently followed Physician Orders for Life Sustaining Treatment for any combination of directives other than full medical treatment and CPR. [25, 26] DNR status may be interpreted as intent to avoid other life-sustaining therapies, such as intubation, despite the fact that many patients who are documented as DNR/DNI express a desire to be intubated for more readily reversible processes such as pneumonia and angioedema. [27] Given the importance to patients of outcomes when weighing medical interventions, it is vitally important that providers capture the disparate indications and outcomes for MV and CPR when discussing code status.…”
Section: Discussionmentioning
confidence: 99%